2016
DOI: 10.7845/kjm.2016.6060
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of lactic acid bacteria for use as silage additives

Abstract: Sixteen lactic acid bacterial strains were isolated from silage and cow dung samples, and characterized to identify their potential as silage additives. They were identified as the members of the genera Lactobacillus, Enterococcus, and Weissella, and clustered into nine groups based on the sequences of the genes for 16S rRNA, RNA polymerase alpha subunit, 60-kDa heat shock protein, and phenylalanyl-tRNA synthase alpha subunit. Among them, the three strains which were genetically similar to L. plantarum showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…3). The decrease in pH may be attributed to the production of organic acids such as lactic acid, acetic acid, and propionic acid, as reported in previous feed fermentation studies [19,23]. The maintenance of a pH level of 4.3 can be explained by LAB utilization of sugars originating from hemicellulose breakdown, causing a decrease in pH [23].…”
Section: Ph Changes During Fermentation At Different Temperaturessupporting
confidence: 53%
See 3 more Smart Citations
“…3). The decrease in pH may be attributed to the production of organic acids such as lactic acid, acetic acid, and propionic acid, as reported in previous feed fermentation studies [19,23]. The maintenance of a pH level of 4.3 can be explained by LAB utilization of sugars originating from hemicellulose breakdown, causing a decrease in pH [23].…”
Section: Ph Changes During Fermentation At Different Temperaturessupporting
confidence: 53%
“…It also stabilizes gastric and intestinal pH and increases animal weight gain by improving fiber digestibility [14][15][16][17]. It has been reported that probiotic feed reduces harmful microorganisms in the intestine, increases beneficial microorganisms by improving the gut microenvironment [12], enhances digestion and absorption of feed, and reduces odor emissions from manure [18,19]. Furthermore, S. cerevisiae has mycotoxin removal ability and can tolerate salivary and gastrointestinal environments [20].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations